Difficulties in Learning English Faced by Visually Impaired Student at Inclusive School - Gunadi, Yogie Febrian; Binawan*, Heribertus (Universitas Syiah Kuala, 2023)
This study was aimed to comprehensively describe the difficulties in learning English faced by a visually impaired student at an inclusive school in Sleman. This study is a descriptive qualitative research in the form of a case study. This research used depth interviews to collect the data about challenges in mastering the four skills in learning English and how he had to deal with them. The result shows that there are two types of difficulties namely internal and external difficulties. Internal difficulties are the difficulties which come from the visually impaired student itself and external difficulties are the difficulties which come from outside such as the teacher, peers, material, and classroom atmosphere.